PROSES PENYELESAIAN SENGKETA IMPOR AYAM BRASIL DI INDONESIA MELAUI WORLD TRADE ORGANIZATION (WTO) TAHUN 2014-2017 - Ilustrasia Wirafahmi; Yessi Olivia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research explains about the role of WTO in settling the trade dispute between Brazil and Indonesia on the issue of chiken imports. Indonesia has been known to be the world’s 10th largest chicken meat consumer in 2015. Brazil, in this case, sued Indonesia to the WTO because Indonesia’s policies of requiring halal labeling and other non-tariff regulations regarding chicken imports were considered as violations to WTO regulation regarding non – tariff barrier.            This research is a qualitative research that uses the descriptive explanative method. The perspective used in this research is the neoliberal institutionalism,  which argues that states created international instistutions to further cooperation and to assist them in solving their problems. The data for this research have been collected from books, articles, journals, documents (published by the governments and WTO), and websites.             This research shows that Brazil and Indonesia have settled their dispute through the Dispute Settlement Body (DSB) and followed by a bilateral negotiation outside the DSB of WTO. For the WTO’s DSB dispute resolution mechanism Indonesia have been stated to be guilty in the panel and have not submitted an  appeal regarding this case. And for the bilateral negotiation outside DSB WTO Indonesia have agreed to renegotiate trade relations with Brasil.Keywords: trade dispute resolution, WTO’s Dispute Settlement Body (DSB), non-tariff barier